Sequential Landfall of Tropical Cyclones in the United States: From Historical Records to Climate Projections. Issue 21 (10th November 2021) - Xi, Dazhi; Lin, Ning
Abstract: In this study, we examine sequential landfalling tropical cyclones (TCs) along U.S. East and Gulf Coasts. We find that Florida and Louisiana are most prone to sequential landfall risk. The minimal time between sequential landfalling TC has decreased for most regions since 1979, although the trend is not statistically significant given limited data. A climate projection indicates a significant increase in sequential landfalls over the 21st century under the SSP5 8.5 scenario, with the chance of a location experiencing a less‐than‐10‐day break between two TC impacts being doubled for most regions. The increases in sequential landfalls in the historical period and projected future climate are both related to increased landfall frequency, even though the storm season has been slightly expanding and may continue to expand. This study highlights a new type of TC hazard resulting from the temporal compounding of landfalls and urges the improvement of coastal resilience. Plain Language Summary: Sequential landfalling tropical cyclones (TCs), which make landfall near a location within a short period of time, can be hazardous for coastal communities. Analyzing the historical records for the U.S. East and Gulf Coasts, we find that the states of Florida and Louisiana are most prone to sequential TC hazard, and this hazard has had an increasing potential for most coastal regions since 1979. Performing future projections of TCs under the effect of climate change, we find that the sequential TC hazard may increase even more significantly in the future. The increased sequential TC hazard in both the historical period and a projected future climate is related to the increased annual frequency of landfalling TCs. This study highlights a new type of TC hazard resulting from the temporal compounding of landfalling TCs and urges the improvement of coastal resilience, e.g., shortening the time scales for infrastructure recovery after TC landfalls. Key Points: Time intervals between sequential landfalling tropical cyclones (TCs) has decreased for most US regions, although the trend is not statistically significant A climate downscaling projection indicates that intervals between sequential US landfalling TCs may significantly decrease in the future The decreased intervals and increased chances of sequential landfalling TCs are mainly driven by increases in storm landfall frequency